The Effect of Price, Product Quality, Brand Awareness, and Brand Image on Purchase Decision and Repeat Purchase (A Case Study on Ultra Milk Packaged Liquid Milk Consumers in Surabaya) - Akhmad Ismu Fajar; Mochamad Tutuk Safirin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of price, product quality, brand awareness, and brand image on purchasing decisions and repurchases of Ultra Milk brand packaged liquid milk products in Surabaya city. The research background is based on a significant decline in Ultra Milk's market share from 2020 to 2024, which indicates a shift in consumer preferences. In the context of an increasingly competitive liquid milk market, understanding the factors that influence consumer behavior is crucial for companies to maintain customer loyalty and improve their marketing strategies. This study uses a quantitative method with a Structural Equation Modeling (SEM) approach to analyze the relationship between these variables. Data was collected through an online questionnaire distributed to consumers who have made more than one purchase. The results showed that all independent variables of price, product quality, brand awareness, and brand image have a significant influence on purchasing decisions, while purchasing decisions themselves have a direct impact on repurchase decisions.